Distribuição de água e fertilizante no solo em coqueiral microirrigado. - Camboim Neto, Luís de França (1995)
A field study was conducted at the seacoast of Itarema, Ceará, Brazil, to evaluate water and fertilizer distribution in the soil of a coconut plantation. The potassium ion was used as a tracer to detennine unifonnity of distribution of water and fertilizer by the irrigation system and predict water and fertilizer distribution within the soil profile. Analysis of the efectiveness of the system in satisfying the water and fertilizer needs of the crop was also done. Samples of the solution water plus fertilizer were collected at the exit of the fertilizer tank and at 64 different places (emitters) on the lateral lines, representing the most and the least favorable hydraulic conditions within the system. Soil samples, to trace the limits of the wet bulbs, vvere collected at points covering a section of the wet volume, one meter on both sides and 1.40 m of depth from the surface of the soil, at 0.20 m increments. In conclusion, it was found that there vvere misconceptions in the original project conceming discharge, time of application and positioning of the emitters in relation to each coconut plant. The management of the system was also found to be inadequate, with a great number of emitters displaced trom the ideal location and in lack of use of the fertilizer injection equipment. Although good water distribution indexes were found (above 85% for CUC and PE) for the system, the water distribution in the soil was found to be poor, as indicated by the vvet bulb graphs. As the fertilizer distribution folIows, approximately, the same pattems for the water distribution, it is valid to predict that fertilizer distribution within the soil of the area would have also been poor, if the fertilizer injection device had been used. A relatively high average annual rainfall on the area tends to reduce the adverse effects of the misconceptions and bad management of the irrigation system, although the actual productivity of the plantation is far from predicted.